The Impacts of Tourism and Governance on CO2 Emissions in Selected South Asian Countries. - Zubaria Andlib; Julio Salcedo-Castro (ETIKONOMI, 2021)
Due to the increase in international connectivity and technological advancement, tourism has gained immense momentum in the recent past. Despite its favorable impacts, tourism has proved to be one of the significant contributors to increasing CO2 emissions.  This study attempts to understand better the relationship between tourism, governance, and the CO2 emissions nexus in selected South Asian countries. The study obtained data from WDI and applied FMOLS, DOLS, and FEOLS methods from 1995-2019. It is observed that tourism has a significant and positive impact on CO2 emissions in the case of selected South Asian countries. Concerning the impact of governance on CO2 emissions, it is observed that governance effectiveness is negatively associated with CO2 emissions. It is evident from the empirical analysis that CO2 emissions can be mitigated with effective government policies. Furthermore, it is also suggested that the government aim at effective environmental policies, and attention should be given to sustainable tourism in the case of South Asian economies.JEL Classification: Q50, Q56, Q58How to Cite:Andlib, Z., & Salcedo-Castro, J. (2021). The Impacts of Tourism and Governance on CO2 Emissions in Selected South Asian Countries. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.17499.